Exenatide Induces Impairment of Autophagy Flux to Damage Rat Pancreas. Issue 1 (January 2017) - Li, Zhiqiang; Huang, Lihua; Yu, Xiao; Yu, Can; Zhu, Hongwei; Li, Xia; Han, Duo; Huang, Hui
Abstract : Objectives: The study aimed to explore the alteration of autophagy in rat pancreas treated with exenatide. Methods: Normal Sprague-Dawley rats and diabetes-model rats induced by 2-month high-sugar and high-fat diet and streptozotocin injection were subcutaneously injected with exenatide, respectively, for 10 weeks, with homologous rats treated with saline as control. Meanwhile, AR42J cells, pancreatic acinar cell line, were cultured with exenatide at doses of 5 pM for 3 days. The pancreas was disposed, and several sections were stained with hematoxylin-eosin. Immunohistochemistry was used to measure the expressions of glucagon-like peptide 1 receptor (GLP-1R) and cysteine-aspartic acid protease-3 in rat pancreas, and Western blot was used to test the expressions of GLP-1R, light chain 3B-I and -II, and p62 in rat pancreas and AR42J cells. The data were expressed as mean (standard deviation) and analyzed by unpaired Student's t -test. Results: Exenatide can induce pathological changes in rat pancreas. The GLP-1R, p62, light chain 3B-II, and cysteine-aspartic acid protease-3 in rat pancreas and AR42J cells treated with exenatide were significantly overexpressed. Conclusions: Exenatide can activate and upregulate its receptor, GLP-1R, then impair autophagy flux and activate apoptosis in the pancreatic acinar cell, thus damaging rat pancreas.